Concomitance of migraine and occipital neuralgia: importance of recognition and treatment for the control of both - Reis, Taianara Sampaio; Nakamura, Gabriela Yumi; Romano, Danielle; Borges , Sabrina; Fernandes, Melissa; Karperjany, Natália; PS Filho, Amauri (Headache Medicine, 2024)
INTRODUCTION: The concomitance of migraine and occipital neuralgia is a rare but significant clinical challenge. Occipital neuralgia often presents with intense, continuous pain that can be mistaken for other headache disorders, complicating diagnosis and treatment. Identifying and managing refractory migraine, especially when complicated by occipital neuralgia, requires a comprehensive understanding of preventive treatments and their limitations. The difficulty in treating such conditions underscores the importance of using evidence-based interventions, such as occipital nerve stimulation and peripheral nerve blocks, which have shown efficacy in reducing headache severity and improving patients quality of life. The rarity and complexity of these conditions demand careful diagnostic and therapeutic strategies to achieve optimal outcomes. Effective pain management strategies, including nerve blocks and nerve stimulation, have proven beneficial for many patients, highlighting the critical need for accurate diagnosis and tailored treatment plans. OBJECTIVE: Describing and recognizing a rare pathology. CASE REPORT: Patient: Female, 32-year-old, diagnosed 5 years ago with partially controlled Chronic Migraine, developed a refractory condition after the sudden onset of a lancinating pain in the right occipital region, of short duration, radiating to the vertex. The migraine, characterized by right hemicrania of moderate intensity, nausea, vomiting, phonophobia, and photophobia, worsened significantly. Imaging studies (CT and MRI of the brain) and neurological examination were normal, except for pain on palpation at the base of the right occipital region (Tinel sign), leading to a diagnosis of Right Occipital Neuralgia. In addition to treatment with Topiramate, a block of the greater and lesser occipital nerves was performed and Gabapentin was introduced, resulting in substantial improvement of both pains. The occipital nerve block was repeated at any sign of worsening occipital pain. Occipital neuralgia, rare and concomitant with other headaches, tends to exacerbate pain and complicate the control of primary headache. CONCLUSION: Occipital neuralgia, rare and concomitant with other headaches, tends to exacerbate pain and complicate the control of primary headache. In this case, the coexistence of chronic migraine and occipital neuralgia required a multifaceted treatment approach. Evidence-based interventions such as occipital nerve stimulation and peripheral nerve blocks played a crucial role in managing the patient's symptoms and improving her quality of life. This case underscores the importance of accurate diagnosis and individualized treatment plans in managing complex headache disorders, emphasizing the need for continued research and clinical awareness of such rare conditions to enhance patient outcomes.